Effect of the Yield Criterion of Matrix on the Brittle Fracture of Fibres in Uniaxial Tension of Composites - Sergei Alexandrov; Yaroslav Erisov; Fedor Grechnikov (Advances in Materials Science and Engineering)
This paper examines the effect of the yield criterion of the matrix on brittle fracture of the fibre in continuous fibre reinforced metal matrix composites subjected to tension in the direction parallel to the fibres. It is assumed that the matrix obeys quite a general isotropic yield criterion. An approximate approach to predicting the tensile load at which the fibre breaks previously proposed in the literature is adopted. It is shown that this tensile load is practically independent of the yield criterion of the matrix. This is a great advantage for engineering applications since an analytic solution is available in the case of Tresca yield criterion. This solution can be used for a wide range of matrix materials with no loss of the accuracy of the prediction of the tensile load at which the fibre breaks.